THE ROLE OF SOCIAL MEDIA ON SPONSORSHIP ACTIVATION - Mihai Constantin Răzvan BARBU; George Bogdan BURCEA; Dragoş Laurenţiu DIACONESCU; Marius Cătălin POPESCU; Leonardo Daniel PĂSĂRIN; Paula APOSTU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2021)
Globally, sponsorship has grown impressive over the last 30 years, receiving an increased importance in the communication mix of companies. Sport organizations have understood the importance and the role sponsorship it plays for the financial support they need. Sponsorship is the material support of an event, activity or organization by an unaffiliated partner. It is a good way to increase brand awareness, which helps to generate consumer preferences and promote brand loyalty and also improves the brand image. Brands play an important role in the development of companies because they bring a number of benefits to them. The paper "Innovation’s impact on sponsorship activation" aims to present a series of theoretical elements of activating sponsorship, as well as the element of innovation in this process, an element represented by the social media presence in our lives and in the last part of the paper is presented a study based on a survey on our topic.